Trapped in a Maze: Arab Teachers in Israel Facing Child Sexual Abuse Among Their Pupils - Sigad, Laura I. (Journal of interpersonal violence, 2022)
Cultural contexts are formative of and fundamental to how individuals understand, conceptualize, and act within a context of violence. Conceptually and methodologically, however, research from a culturally informed perspective on the experiences of teachers contending with the violence of child sexual abuse (CSA) in particular is broadly limited. As educators frequently confront cases of CSA in their everyday work, their ability to promote detection, disclosure intervention, and especially prevention gives them the potential to be agents of social change; however, while their responsibilities are critical, they are simultaneously members of their communities and cultures, and their interactions are bound by these dynamics. The purpose of the study is to analyze the experiences of Arab teachers in Israel who confront CSA in their everyday work. The findings are based on qualitative thematic analysis of semi-structured interviews conducted with 30 female Arab teachers working within the Arab school system in Israel. Results indicate that when facing CSA, the teachers experience an ongoing conflict between their cultural and professional codes, trapping them in a maze of intertwining and oppositional demands. On the one hand, they are constrained by the norm of protecting the honor and maintaining the status and reputation of those involved, including themselves; on the other hand, as empathetic professionals, they desire to aid their pupils. While the participants do not accept the status quo, they are effectively at a loss as to how to change it. In order find a way out of their entrapment in coping with CSA among their pupils, the only currently available path is to act as a lone hero; there is, however, the potential to foster the development of a secondary culture within the school to inaugurate cultural change in coping with CSA. Implications for future research, policy, and practice are discussed.